(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Aims: For decades, cosmetics gained a lot of importance; a day, it would be indispensable for the mankind to maintain health and hygiene with appearance. In the category of cosmetic products, the present investigation focused on lip balm which is a type of lip cosmetics. The aim is to formulate and evaluate the novel lip balm. Materials and Methods: By using ingredients such as beeswax, shea butter, cocoa butter, coconut oil, almond oil, glycerin, orange oil, and a coloring agent. The beeswax was used as a base, and for glossiness, shea butter and cocoa butter as an emollient, coconut oil and almond oil as moisturizing agents, glycerin for a glossy and moisturizing agent, orange oil as a flavoring agent, and turmeric as a coloring agent. A total of 8 formulations were prepared with different compositions ranging from F1 to F8 to select the best formulation for the future scope of study. The prepared formulation for evaluated for suitable parameters such as determination of pH, skin irritation, perfume stability, spreadability, melting point, and breaking point. Results and Discussion: All the formulations show a yellow color appearance with a pleasant odor. The pH for F1 to F8 was in the range of 6.2–6.5, a melting point of 60°–66°C, and a breaking point of 28 g–32 g. All the formulations do not show any skin irritation and spreadability shows from average to very good. Conclusion: By considering the results of all the parameters, the F8 formulation was selected as the best formulation. Hence, the F8 formulation met the objective of the present study which may hold promise for future studies